1996
DOI: 10.1007/bf00017800
|View full text |Cite
|
Sign up to set email alerts
|

The pc-1 phenotype of Chlamydomonas reinhardtii results from a deletion mutation in the nuclear gene for NADPH:protochlorophyllide oxidoreductase

Abstract: The pc-1 mutant of Chlamydomonas reinhardtii has been shown to be incapable of protochlorophyllide photoconversion in vivo and is thought to be defective in light-dependent NADPH:protochlorophyllide oxidoreductase activity. We have isolated and characterized the nuclear genes encoding this enzyme from wild-type and pc-1 mutant Chlamydomonas cells. The wild-type CRlpcr-1 gene encodes a 397 amino acid polypeptide of which the N-terminal 57 residues comprise the chloroplast transit sequence. The Chlamydomonas pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 84 publications
(138 reference statements)
1
29
0
3
Order By: Relevance
“…The phenotypes of pcy1-1 and pcy1-2 can be accommodated within this model. A similar phenomenon was noted in strain pc-1 for the Lpcr1 transcript, which has a frameshift at the fourth codon resulting from a 2-nucleotide deletion (54). On the other hand, the dissimilar phenotype of pcy1-3 is surprising.…”
Section: Discussionsupporting
confidence: 60%
“…The phenotypes of pcy1-1 and pcy1-2 can be accommodated within this model. A similar phenomenon was noted in strain pc-1 for the Lpcr1 transcript, which has a frameshift at the fourth codon resulting from a 2-nucleotide deletion (54). On the other hand, the dissimilar phenotype of pcy1-3 is surprising.…”
Section: Discussionsupporting
confidence: 60%
“…These include mutants of both the light-and the dark-dependent protochlorophyllide reductases (POR1 and DPOR) of the Mg-PPIX methyltransferase (CHLM) and of the three subunits of Mg chelatase (CHLH1, CHLI1/2, and CHLD). These mutants are photosensitive, severely chlorotic, and/or yellow in the dark (Li and Timko, 1996;Chekounova et al, 2001;Falciatore et al, 2005;von Gromoff et al, 2008;Meinecke et al, 2010;Grovenstein et al, 2013). It was recently demonstrated that the specific loss of chlorophyll b in Chlamydomonas does not disrupt accumulation of LHCI and LHCII polypeptides as long as chlorophyll a biosynthesis remains intact (Bujaldon et al, 2017).…”
Section: Phenotypic Similarities Of Chlorophyll Biosynthesis Mutants mentioning
confidence: 99%
“…In C. reinhardtii, there is both a light-dependent and a light-independent pathway for the conversion of protochlorophyllide to chlorophyllide (28). The pc1 y7 double mutant is blocked in both pathways, leading to the accumulation of protochlorophyllide and inability to grow under even LL conditions (57). In the presence of light, accumulated protochlorophyllide can act as an endogenous photosensitizer and generate 1 O 2 ‫ء‬ within the chloroplast (63).…”
Section: Vol 6 2007 Acclimation To Singlet Oxygen 923mentioning
confidence: 99%